If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7n + -1(1 + 3n) = -8 7n + (1 * -1 + 3n * -1) = -8 7n + (-1 + -3n) = -8 Reorder the terms: -1 + 7n + -3n = -8 Combine like terms: 7n + -3n = 4n -1 + 4n = -8 Solving -1 + 4n = -8 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 4n = -8 + 1 Combine like terms: -1 + 1 = 0 0 + 4n = -8 + 1 4n = -8 + 1 Combine like terms: -8 + 1 = -7 4n = -7 Divide each side by '4'. n = -1.75 Simplifying n = -1.75
| -5x+4(-3+4x)=-10.8+10.6x | | x(x+0.3)=5.6 | | 81y-8x=-65 | | X+28+x+36=64 | | x^6-125y^9= | | 4x+1/x-1=20x-3/5x-7 | | -5/2-6+9 | | 4(6x+10)=-2(x-2) | | (4/x-7)-(5/x+7)=(2/x^2-49) | | log(8)(5x+5)=log(8)(5x+2) | | 8-1/2n=12 | | (-6+34)/(-14)+2 | | f(x)=4x^2+7x-15 | | (X/2)-(2/3)=(1/4) | | 8-5x=38 | | 2/7x=-6/35 | | 2(1.5c+4)=(-1) | | 5+5(2-x)=-3(x+5) | | a/4+4=88 | | x^2-2=5x^2-12x-2 | | 4+5(2-x)=-2(x+5) | | 10v^2-53v+36=0 | | y=2x^2-11x+9 | | (X^2+9x+20)/(x+15) | | f(x)=5x^2-6x-8 | | f(x)=5x^2-6x-8 | | 3x+17y=-23 | | D=Prk | | 8x+4=26-2x | | 4(3+x)=5(4x-1)-47 | | 9z+5-2z=59-2z | | 8x-2(2-x)=13 |